2020
DOI: 10.1016/j.jaci.2019.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Allergic disease, corticosteroid use, and risk of Hodgkin lymphoma: A United Kingdom nationwide case-control study

Abstract: Risk of Hodgkin's Lymphoma in allergic disease Hodgkin's Lymphoma Immune suppression Corticosteroids Eczema Asthma Allergic rhinitis 1.4 x 95%CI(1.2-1.6) p<0.001 6.1 x 95%CI(3.0-12.3) p<0.001 1.9 x 95%CI(1.3-2.7) P<0.001 1.1 x 95%CI(0.9-1.3) P=0.56 1.2 x 95%CI(1.0-1.5) P=0.016 1.4 x 95%CI(1.2-1.7) p<0.001 Infectious mononucleosis Background: Immunodeficiency syndromes (acquired/ congenital/iatrogenic) are known to increase Hodgkin lymphoma (HL) risk, but the effects of allergic immune dysregulation and cortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 50 publications
(65 reference statements)
2
19
0
5
Order By: Relevance
“…3 The article in this issue by Rafiq and co-authors from the UK confirms previously accepted associations between development of HL and steroids or immunosuppression and suggests an extension of the relationship between HL and immunologic dysregulation by recognizing an association between asthma or eczema and HL. 4 This finding adds allergic conditions to the previously acknowledged immunologic anomalies of autoimmune, infection, and immunosuppression. The authors are to be commended for using ''big data'' to uncover this small but potentially valuable finding.…”
mentioning
confidence: 76%
“…3 The article in this issue by Rafiq and co-authors from the UK confirms previously accepted associations between development of HL and steroids or immunosuppression and suggests an extension of the relationship between HL and immunologic dysregulation by recognizing an association between asthma or eczema and HL. 4 This finding adds allergic conditions to the previously acknowledged immunologic anomalies of autoimmune, infection, and immunosuppression. The authors are to be commended for using ''big data'' to uncover this small but potentially valuable finding.…”
mentioning
confidence: 76%
“…Therefore, for both drugs, there is no support for the initial hypothesis that they increase the risk of long-term cancer in children with AD [ 55 , 56 ]. A further and recent study has also highlighted a relationship between allergic diseases, use of corticosteroids and Hodgkin's lymphoma, reporting how immunosuppression was associated with a 6 times greater probability of lymphoma, with minimal change after adjustment for the use of corticosteroids [ 57 ]. Furthermore, it has recently been shown that there is no relationship between the risk of keratinocyte tumors and the use of TCIs [ 58 ].…”
Section: Appendixmentioning
confidence: 99%
“…The risk of CHL development is associated with socioeconomic status, especially among AYAs [ 4 , 9 ]. High socioeconomic status and lack of exposure to microorganisms during childhood have been suggested to increase the risk of NSCHL development [ 10 , 11 ]. Conversely, MCCHL in the AYA age group—which corresponds with a high prevalence of EBV infection—is predominant in developing countries, and its morbidity decreases with economic development [ 12 ].…”
Section: Classical Hodgkin Lymphomamentioning
confidence: 99%